Mechanistic Determinants of Antibacterial Potency in Libyan and Saudi Monofloral Honeys: Integrated H₂O₂, Acidity, and Phenolic Chemistry - Alwashaish, Mohanned; Abushalla , Faraj; Abusiksaka , Abdulmutaleb (AlQalam Journal of Medical and Applied Sciences, 2026)
Honey exhibits broad-spectrum antimicrobial activity mediated by multiple complementary mechanisms, including hydrogen peroxide production H2O2, phenolic compounds, and intrinsic acidity. In the era of escalating antimicrobial resistance (AMR), such multifactorial activity represents a promising natural strategy that may reduce the likelihood of resistance development. However, comparative data on the biological properties and mechanistic pathways of Libyan and Saudi honeys remain limited. In this study, 180 monofloral honey samples were analyzed, comprising Libyan varieties (Sidr, Athel, and Hannon) and Saudi varieties (Sidr, Talh, and Sumra). Physicochemical quality parameters were evaluated according to Codex and International Honey Commission standards, while bioactive characteristics were assessed through measurements of total phenolics, antioxidant capacity, and hydrogen peroxide generation kinetics. Antibacterial efficacy was tested against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, with mechanistic contributions further examined using catalase, polyvinylpolypyrrolidone (PVPP), and pH neutralization assays. All samples complied with Codex quality criteria. Libyan Sidr honey demonstrated the highest phenolic content and antioxidant activity, whereas Saudi Talh and Sumra honeys exhibited the greatest H2O2 production. These compositional differences were reflected in antibacterial performance: peroxide-dominant Talh and Sumra showed the lowest minimum inhibitory concentrations (MIC) against S. aureus (10–12.5 % (w/v)), Sidr honeys displayed intermediate phenolic-driven activity, and Athel and Hannon relied primarily on acidity. This integrated comparison provides the first mechanistic linkage between floral origin and antibacterial pathways in Libyan and Saudi honeys, highlighting distinct regional translational potentials, with Saudi Acacia honeys suited as peroxide-driven candidates for topical wound care and Libyan Sidr honeys as phenolic-rich nutraceuticals. By clarifying these mechanisms, the study supports the discovery of natural antimicrobial alternatives and contributes to global efforts to combat AMR.